Mast Cells Density Positive to Tryptase Correlates with Angiogenesis in Pancreatic Ductal Adenocarcinoma Patients Having Undergone Surgery - Michele Ammendola; Rosario Sacco; Giuseppe Sammarco; Giuseppe Donato; Valeria Zuccalà; Maria Luposella; Rosa Patruno; Ilaria Marech; Severino Montemurro; Nicola Zizzo; Cosmo Damiano Gadaleta; Girolamo Ranieri (Gastroenterology Research and Practice)
Background. Literature data suggest that cells such as mast cells (MCs), are involved in angiogenesis. MCs can stimulate angiogenesis by releasing of several proangiogenic cytokines stored in their cytoplasm. In particular MCs can release tryptase, a potent in vivo and in vitro proangiogenic factor. Nevertheless few data are available concerning the role of MCs positive to tryptase in primary pancreatic cancer angiogenesis. This study analyzed MCs and angiogenesis in primary tumour tissue from patients affected by pancreatic ductal adenocarcinoma (PDAC). Method. A series of 31 PDAC patients with stage T2-3N0-1M0 (by AJCC for Pancreas Cancer Staging 7th Edition) was selected and then underwent surgery. Tumour tissue samples were evaluated by means of immunohistochemistry and image analysis methods in terms of number of MCs positive to tryptase (MCDPT), area occupied by MCs positive to tryptase (MCAPT), microvascular density (MVD), and endothelial area (EA). The above parameters were related to each other and to the main clinicopathological features. Results. A significant correlation between MCDPT, MCAPT, MVD, and EA group was found by Pearson’s t-test analysis (r ranged from 0.69 to 0.81; P value ranged from 0.001 to 0.003). No other significant correlation was found. Conclusion. Our pilot data suggest that MCs positive to tryptase may play a role in PDAC angiogenesis and they could be further evaluated as a novel tumour biomarker and as a target of antiangiogenic therapy.